Modeling of milk acidification. Issue 3 (2021) - Robles-Rodriguez, C.E.; Szymańska, E.; Özkan, L.
Abstract: This paper deals with the development of an empirical model to describe the dynamics of milk acidification process for the production of acid casein. The model is based on the dynamics of the pH profiles during the acidification process since pH is a good indicator of the status of the precipitation. Data from laboratory experiments has been used to identify the parameters in the proposed model. Calibration and validation results, with an independent data set, show that the model is able to predict accurately the pH at different temperatures and acid addition rates. Furthermore, the model has been used in a simulation study as an advisory tool to suggest acid addition, proving the parsimony of the model.